The development of self-healing model with massage therapy and exercise therapy for a wrist injury - Nofa Anggriawan; Wara Kushartanti; Wallapa Choeibuakaew; Rina Yuniana (Jurnal Keolahragaan, 2022)
This research aims to produce a model of self-healing with massage therapy and exercise therapy for proper and effective wrist injury for the community to cure wrist injury. This research was a development research with stage: preliminary study and data collection, planning, product draft development, expert validation, product testing, revision and evaluation. The subjects of small-scale test were 5 people, subjects were large-scale test and product effectiveness test was 10 people using minimum sample size formula at FIK UNY Physical Therapy Clinic and Masase Terapi Cedera Olahraga Metode Ali Satia Graha. The instruments used to collect data were expert validation sheets, questionnaire sheets, and goniometers to measure range of movement of wrist joints. The results showed that model of self-healing with massage therapy and exercise therapy in wrist injury was valid. The results of validation of material experts and media experts were included in the high category. Product quality from small-scale tests and large-scale tests was categorized as high. The results of product effectiveness test showed a significant reduction in pain complaints, increased motion function and increased range of movement (ROM). The conclusion of this study was a model of self-healing with massage therapy and exercise therapy valid and effective for a handling wrist injury.